An E-selectin targeting and MMP-2-responsive dextran–curcumin polymeric prodrug for targeted therapy of acute kidney injury. (29th October 2018) - Hu, Jing-Bo; Liu, Di; Qi, Jing; Lu, Kong-jun; Jin, Fei-yang; Ying, Xiao-Ying; You, Jian; Du, Yong-Zhong
Abstract : Based on the overproduction of matrix metalloproteinase-2 (MMP-2) in renal tissue during acute kidney injury (AKI) occurrence, we developed a MMP-2 enzyme-triggered polymeric prodrug with sialic acid (SA) as the targeting group to the inflamed vascular endothelial cells for enhanced therapeutic outcomes. Abstract : Based on the overproduction of matrix metalloproteinase-2 (MMP-2) in renal tissue during acute kidney injury (AKI) occurrence, we developed a MMP-2 enzyme-triggered polymeric prodrug with sialic acid (SA) as the targeting group to the inflamed vascular endothelial cells for enhanced therapeutic outcomes. An MMP-2-responsive peptide, PVGLIG, was used to endow the polymeric prodrug with the ability to rapidly release the anti-inflammatory drug, curcumin (CUR), after the targeted site is reached and to improve the drug concentration in the target tissue. The sialic acid–dextran–PVGLIG–curcumin (SA-DEX-PVGLIG-CUR) polymeric prodrug was successfully synthesized via multi-step chemical reactions and characterized by 1 H NMR. The water solubility of CUR was significantly increased in the polymeric prodrug and was approximately 23-fold higher than that of free CUR. The in vitro drug release results showed that the release rate of SA-DEX-PVGLIG-CUR was significantly enhanced compared to that of SA-DEX-CUR in a dissolving medium containing the MMP-2 enzyme, suggesting that SA-DEX-PVGLIG-CUR had rapid drug release characteristics in an inflammatory environment. A cellular uptake test confirmed that SA-DEX-PVGLIG-CUR was effectively internalized by inflamed vascular endothelial cells in comparison with that by normal cells, and the mechanism was associated with the specific interaction between SA and E-selectin receptors specifically expressed on inflamed vascular endothelial cells. Bio-distribution results further demonstrated the rapid and increased renal accumulation of SA-DEX-PVGLIG-CUR in AKI mice. Benefiting from the rapid drug release in renal tissue, SA-DEX-PVGLIG-CUR effectively ameliorated the pathological progression of AKI compared with free CUR and SA-DEX-CUR, as reflected by the improved renal functions, histopathological changes, pro-inflammatory cytokine production, oxidative stress and expression of apoptosis related proteins. Altogether, this study provided a new therapeutic strategy for the treatment of AKI.